Infrastructure Governance and Corruption : Where Next? - Kenny, Charles (World Bank, Washington, DC, 2012)
Governance is central to development outcomes in infrastructure, not least because corruption (a symptom of failed governance) can have significantly negative impact on returns to infrastructure investment. This conclusion holds whether infrastructure is in private or public hands. This paper looks at what has been learned about the role of governance in infrastructure, provides some recent examples of reform efforts and project approaches, and suggests an agenda for greater engagement - primarily at the sector level - to improve governance and reduce the development impact of corruption. The discussion covers market structure, regulation, state-owned enterprise reform, planning and budgeting, and project design.